Indium slabs induced structural phase transitions and their effects on the electrical and optical properties of stacked layers of the thermally annealed Cu2O thin films - Sabah E. AlGarni; A.F. Qasrawi (Results in Physics, 2020)
In this work, the effects of the structural evolutions caused by the insertion of indium slabs (100 nm) between layers of cupric oxide on the electrical and optical properties are investigated. The stacked layers of Cu2O/Cu2O (CC) which are thermally annealed at 500 °C in a vacuum media is observed to comprise both of the CuO (45.9%) and Cu2O (54.1%) phases in its structure. The major structural phase of CuO and Cu2O are monoclinic and orthorhombic, respectively. Insertion of indium slabs which is followed by thermal annealing reduced the content of CuO to 29.2% and enriched the content of Cu2O to 70.8%. The CC samples exhibited structural phase transitions from monoclinic CuO to hexagonal Cu2O in the presence of indium and under thermal annealing. The insertion of indium slabs in the samples increased the crystallite size and enhanced the optical transmittance. It also decreased the microstrain, the defect density and the electrical resistivity. The donor states are shifted deeper below the conduction band edge. The nature of optical transitions also changed from direct allowed to direct forbidden with a decrease in the energy band gap values from 2.05 to 0.85 eV upon indium slabs insertion followed by annealing process.